Differential Diagnosis and Treatment of Isolated Pathologies of the Sphenoid Sinus: Retrospective Study of 46 Cases - Marcolini, Thomas Ribeiro; Safraider, Maryane Cristine; Socher, Jan Alessandro; Lucena, Guilherme Olinto (International Archives of Otorhinolaryngology, 2015)
Introduction Isolated disease of the sphenoid is rare and has often been overlooked due to its remote location and difficult access.Objective A retrospective study of the main causes of isolated sphenoid sinus diseases with discussion of the most appropriate methods of diagnosis and treatment.Methods A total of 46 cases of isolated sphenoid disease treated between January 2008 and December 2013 were evaluated by objective ear, nose, and throat examination and video endoscopy, computed tomography of the paranasal sinuses, and, in some cases, magnetic resonance imaging. In each case, we decided between drug and/or endoscopic treatment.Results We identified 12 cases of isolated sphenoiditis (26.1%), 3 cases of fungal sphenoiditis (6.5%), 3 cases of sphenochoanal polyps (6.5%), 22 cases of mucocele (47.8%), 2 cases of cerebrospinal fluid leak (4.3%), and 1 case each of meningoencephalocele (2.1%), inverted papilloma (2.1%), fibrous dysplasia (2.1%), and squamous cell carcinoma (2.1%).Conclusion A prevalence of inflammatory and infectious diseases was found, and endoscopic surgery for the sphenoid sinus approach is effective in treating various diseases of the isolated sphenoid, whether complicated or not.
Keywords: sphenoid sinus; paranasal sinuses; sphenoid sinusitis; cerebrospinal fluid leak; paranasal sinus neoplasms